In vitro effects of sex hormones in human meibomian gland epithelial cells. (October 2016) - Schröder, Antje; Abrar, Daniel B.; Hampel, Ulrike; Schicht, Martin; Paulsen, Friedrich; Garreis, Fabian
Abstract: Meibomian gland dysfunction (MGD) is considered the most common cause of dry eye disease (DED). Sex hormones seem to play a role in the pathogenesis of MGD although their involvement is not completely understood. Therefore, in the present study we evaluated the effect of dihydrotestosteron (DHT) and estradiol (β-Est) on an immortalized human meibomian gland epithelial cell line (HMGEC). Protein expression of sex hormone receptors in HMGEC was investigated by western blot. Ultrastructural morphology, Sudan III lipid staining, cell proliferation as well as vitality assays were performed. Furthermore, expression of MGD-associated markers for keratinization (hornerin, involucrin and CK6), proliferation (CK5 and CK14) and lipid synthesis (fatty acid synthase and stearoyl-CoA desaturase) were analyzed by real time RT-PCR. Western blot revealed presence of androgen receptor (AR), estrogen receptors α and -β (ERα, ERβ) and progesterone receptor (PR) in HMGEC. PR, ERα and ERβ expression was significantly induced under cultivation with serum, whereas sex hormones stimulation showed no further effect on protein expression of PR, ERα and ERβ. Our results showed no impact of MGD-associated sex hormones to cellular morphology and lipid accumulation in HMGEC. Cell proliferation was slightly induced through application of sex hormones and supplementation of calcium. However, both sex hormones and calcium altered gene expression of MGD-associated markers. Especially keratinization genes hornerin (HRNR) and cornulin (COR) were induced after application of sex hormones and calcium in serum-free cultivated HMGEC. This may promote keratinization processes that are associated with MGD. Further investigations are necessary to analyze the (hyper)keratinization processes that occur during MGD and using HMGEC as an in vitro model. Highlights: Protein expression of sex hormone receptors in cultivated HMGEC. Expression of progesterone receptor (PR), estrogen receptors (ER)α and -β was induced under cultivation with fetal calf serum. DHT and β-Est had no effect on cellular morphology and lipid accumulation. Sex hormones and calcium altered gene expression of MGD-associated markers, especially keratinization genes .